Characterization of Triphenylamino-Based Polymethine Dyes. (12th May 2013) - Ullah, Saleem; Ahmad, Irshad; Alias, Yatimah; Yusoff, Ismail; Ashraf, Muhammad Aqeel
Abstract : In this high-technology application, age functional dyes especially polymethine dyes have captured much attention of the researchers due to their immense potential for high-tech uses. Polymethine dyes show promising absorption spectra in the visible range, which can be easily exploited for the use of written text copying, photographic imaging, or photothermographic recording materials. Keeping this in mind, our research is composed of an investigation of two triphenylamino-based polymethine dyes, a known polymethine dye 3 and a new one polymethine dye 5, which have been synthesized by the reaction of 4-(diphenylamino) benzaldehyde 2 and 4, 4 ′ -(phenylazanediyl) dibenzaldehyde 4 with 4, 4 ′ -vinylidene-bis(N, N-dimethylaniline) 1. Based on bis-dimethylaminophenylethylene moiety, the new polymethine dye showed more high absorption spectra in the range of 600–700 nm than that of the known polymethine dye based on bis-dimethylaminophenylethylene moiety. Their maximum spectra were exhibited at 637 nm and 653 nm, respectively. Their leuco-converted reversible colored forms were also investigated.